Gambaran Tingkat Pengetahuan dan Dukungan Suami terhadap Keluarga Berencana pada Pedagang Pasar Cikurubuk Kota Tasikmalaya - Reva Amalia; Arumdalu Desri Fitri; Najwa Syifa Nabila Putri; Ismi Tasya Anisa; Aini Syarah Ramadhani; Ajeng Suci Lestari; Vina Sabrina; Agni Khoerunisa (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Awareness and support from husbands toward the Family Planning (FP) program play an important role in determining contraceptive use participation in Indonesia. However, male participation in FP programs remains relatively low, especially in the Tasikmalaya area. Therefore, this study was conducted to describe the level of knowledge and support from husbands regarding the Family Planning program among traders at Cikurubuk Market, Tasikmalaya City. This research employed an observational method with a cross-sectional study design, involving 30 respondents selected through total sampling. Data were collected using a questionnaire and analyzed descriptively. The findings showed that respondents had a good level of knowledge about FP (53.3%) and received support from their husbands in using contraceptives (56.7%), with most information about FP obtained from healthcare workers (56.7%).These findings imply the need to enhance educational programs about Family Planning specifically targeting men, to raise awareness and increase husbands’ involvement, as well as to strengthen the dissemination of information within communities, especially in workplaces and other informal work environments.